Praktik Sewa Menyewa Rental Mobil Dump Truck Ditinjau Dari Ekonomi Syari’ah Di CV. Tunggal Perkasa Purwakarta - Abdul Rouf; Ahmad Saepudin; Siti Rohmat (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
A development of the leasing business, such as renting a car at CV Tunggal Perkasa which is engaged in car rental services in the field of expeditions, in this lease there is an agreement where this lease creates rights and obligations for both parties. In Islam, leasing is termed al-ijarah, which is a contract for the transfer of usufructuary rights over goods or services, through payment of rental wages, without being followed by a transfer of ownership (milkiyah) of the goods themselves. The purpose of this study was to determine the practice of renting a car rental service at CV. Tunggal Perkasa, and to find out an overview of the sharia economy in leasing at CV. Mighty Single. The type of research used is field research, while the approach used in this research is a descriptive-qualitative approach. The mechanism used in the practice of renting a dump truck is to enter into a contract agreement with predetermined terms and conditions, and the rental system applied to both parties is bound. When viewed from the perspective of the contract, the pillars and terms of the lease are reviewed according to the Fatwa of the National Sharia Council-Indonesian Ulema Council NO: 112/DSN-MUI/IX/2017. The lease agreement made by both parties is not in accordance with Fiqh Ijarah